Strategi Pemberian Gizi untuk Mencegah Stunting pada Masyarakat Miskin di Kelurahan Titi Rantai - Panggabean, Noviyantika Azzahra; Ginting, Bengkel; Ritonga, Fajar Utama (Medan Resource Center, 2023)
This article aims to discuss nutrition strategies to prevent stunting in poor communities in Kelurahan Titi Rantai. Stunting is a serious public health problem, especially in areas with high poverty rates such as Kelurahan Titi Rantai. This study aims to develop an effective nutrition strategy to prevent stunting among the poor in the kelurahan. The approach used was a qualitative and quantitative analysis of nutritional needs and the social and economic factors that influence access to adequate nutrition. The results of this study are expected to provide guidance for policy makers and health practitioners in stunting prevention efforts at the local level.